Konsep Makna Nggawa ‘Membawa’ dalam Bahasa Jawa : Kajian Linguistik Kognitif - Mahanani, Endah Normawati (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2025)
This article discusses the concept of the meaning of ngawa 'bring' in Javanese. The exact concept is related to the image produced. The term ngawa 'bring' in Javanese has different pronunciations, adjusted to the object being carried, the method of bringing it, the tool used, and the time of bring the object. The method used in this article is the simak method for data collection. Data were analyzed using the agih method with the direct element division technique, and presented using an informal method. The results of the analysis in this article are the acquisition of 18 terms that are peripheral to the categorization of ngawa 'bring'. Based on this analysis, it can be seen that ngawa 'bring' is the central element, while nyangking, nyangklèk, nyangklong, nyunggi, mikul, nggendhong, mbopong, mondhong, manggul, ngindhit, nggêgêm, nyêkithing, nyêngkiwing, nyèrèt, ngêmban, ngêmpit, ngotong-otong, and nuntun are its peripheral elements. The central and peripheral elements in the data as a whole constitute the verb category formed by the affixation process. This affixation process involves the addition of a nasal to the base form, or can be formulated as follows: N (m, n, ng, and ny) + base. Keywords: ngawa, categorization, linguistics cognitive.